Super‐Intense Geomagnetic Storm on 10–11 May 2024: Possible Mechanisms and Impacts - S. Tulasi Ram; B. Veenadhari; A. P. Dimri; J. Bulusu; M. Bagiya; S. Gurubaran; N. Parihar; B. Remya; G. Seemala; Rajesh Singh; S. Sripathi; S. V. Singh; et al. (Space Weather)
Abstract One of the most intense geomagnetic storms of recent times occurred on 10–11 May 2024. With a peak negative excursion of Sym‐H below −500 nT, this storm is the second largest of the space era. Solar wind energy transferred through radiation and mass coupling affected the entire Geospace. Our study revealed that the dayside magnetopause was compressed below the geostationary orbit (6.6 RE) for continuously ∼6 hr due to strong Solar Wind Dynamic Pressure (SWDP). Tremendous compression pushed the bow‐shock also to below the geostationary orbit for a few minutes. Magnetohydrodynamic models suggest that the magnetopause location could be as low as 3.3RE. We show that a unique combination of high SWDP (≥15 nPa) with an intense eastward interplanetary electric field (IEFY ≥ 2.5 mV/m) within a super‐dense Interplanetary Coronal Mass Ejection lasted for 409 min–is the key factor that led to the strong ring current at much closer to the Earth causing such an intense storm. Severe electrodynamic disturbances led to a strong positive ionospheric storm with more than 100% increase in dayside ionospheric Total Electron Content (TEC), affecting GPS positioning/navigation. Further, an HF radio blackout was found to occur in the 2–12 MHz frequency band due to strong D‐ and E‐region ionization resulting from a solar flare prior to this storm.